Development of Drainage Cleaning Machine with Virtual Simulation - Chai, Hao Wei; Jafferi, Noormaziah (Research Progress in Mechanical and Manufacturing Engineering, 2022)
Drainage is one of the things that need to be taken into account when planning a town. It is important in ensuring the flow of wastewater from the residential areas is carried out to a properly sewerage system. The dumping of physical rubbish into drains has led to an increase in cases of blockage drains and has led to the issue of flash floods in major cities across the country. In addition, drain cleaning tasks in Malaysia still rely on inefficient manual labor and there is no element of sustainability in these operations for the long term in the future. Therefore, the aim of the project is to develop an automated drainage cleaning machine that can remove the solid waste that flow with the drain water with virtual simulation. This machine is design based on the specific dimension of drain and can easily installed at the drain. This machine has two mechanisms to achieve the cleaning purpose which is the rotation and the push and pull mechanism. After the design phase, the full assembly of drainage cleaning machine has completed the simulation which was conducted by the SolidWorks. With the result obtained from the simulation and analysis, The time taken for a complete cycle of the cleaning operation is 25 seconds where it is capable of lifting 15kg of solid waste. It is operating for 1 hour, as much as 144kg of solid waste can be cleaned from the drainage. The appropriate recommendation is that this machine is set to lift the solid waste out to side of machine every 30 minutes regularly to ensure the optimal operation of cleaning and energy saving.